Strand 3: Securing the Safety Net: Towards a Coherent Strategy for Embedding Networked Learning in Academic Staff Development - Tickner, Sue (Proceedings of the International Conference on Networked Learning, 1998)
This paper considers the ’critical factors’ involved in effective implementation of Networked Learning. These factors are examined within the institutional context of recent developments and future plans for academic professional development at the University of Glasgow. The importance of ensuring a supportive institutional framework is discussed and some advantages of the University of Glasgow’s specific culture are identified, as are some outstanding problem areas and our strategies for overcoming these. However, in times of change there will never be a perfect moment of stasis where all elements are balanced; this realisation is as important as any other.